(3QSGdI aj GdOdGdI Ydi GdHYK gd gi YbdjI Ch fbdjIs - (3eMeO GdSYjO Hf eMjj GdOjf GdMSfj GdLRGFQj,J (B1278 (3g` s ((3YHO GdbGOQ Hf eMeO Hf jYbhH s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdehJ hGdMjGI djHdhce Cjce CMSf YedkG ef Yed UGdMkG adfaSI hef CSGA aYdjgG s
(3BNQgG (B:s
(3hbGd GdEeGe GHf YQaI GdOdGdI Ydi GdBNQI SeYjI hdG eLGd ddYbd ai Pdc hdG jSJbd HEKHGJgG bGd eDda hcJH HChGFd QLH ef YGe (B1278 s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds